Presenting a suitable model for selecting the board members in economic companies of bonyad Ta'avon Vedja Organization - Moslem Moradzadeh; Komeil Mahjori (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Companies board at the top of every company and play key parts in every system of corporate governance. As a result, this issue makes the board of directors the current focal point of various efforts to improve corporate governance Therefore, corporate governance experts have been looking for a long time to improve the composition of the board of directors and evaluate them with new models; In this way, the boards of directors can act more effectively. Therefore, the purpose of this research is to present the local model for selecting the board members in Subsidiaries of Bonyad Ta'avon Vedja Organization.Methodology: In this research, the mixed approach of theme analysis, factor analysis and fuzzy Delphi method was used to identify themes. In the sample group in thematic analysis, 8 semi-structured interviews were conducted with faculty members, board members and major stakeholders. In the fuzzy Delphi sample group, 15 people were selected as experts to answer the questions of the questionnaire. In the quantitative approach of factor analysis, a sample group of 200 people has been used.Findings: The results of the board selection checklist showed 84 primary codes that were classified into 6 organizing themes. The main organizing themes of the board members selection checklist are: intelligence, skill, psychological, experience, literacy and structural and demographic.Originality/Value: Therefore, the results show that the selection of board members based on the themes identified according to the identified checklist will have a better performance ahead.